Liangzhi and Conscience: Intercultural Grammars of Moral Knowing between China and the West - Miranda, Nuno (E- Revista de Estudos Interculturais, 2026)
This study explores how moral understanding is shaped by language and culture, using the encounter between the Chinese concept of liangzhi and Western notions of moral conscience as a point of departure. It argues that these frameworks do not merely represent different ethical theories but sustain distinct ways of speaking, reasoning, and feeling about the moral life. The paper proposes that intercultural dialogue should therefore be approached as a process of linguistic clarification rather than conceptual translation. By examining how moral knowledge functions within different “forms of life,” it suggests that the work of intercultural philosophy lies not in reconciling traditions but in learning to communicate across their moral grammars. Such dialogue transforms ethical universality from a single system into a shared yet plural field of meaning.